1988
DOI: 10.3758/bf03203833
|View full text |Cite
|
Sign up to set email alerts
|

Micro Experimental Laboratory: An integrated system for IBM PC compatibles

Abstract: Micro Experimental Laboratory (MEL)is a third-generation integrated software system for experimental research. The researcher fills in forms, and MEL writes the experimental program, runs the experiments, and analyzes the data. MEL includes a form-based user interface, automatic programming, computer tutorials, a compiler, a real-time data acquisition system, database management, statistical analysis, and subject scheduling. It can perform most reaction time, questionnaire, and text comprehension experiments w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
508
0

Year Published

1996
1996
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 753 publications
(509 citation statements)
references
References 11 publications
1
508
0
Order By: Relevance
“…A control experiment, in which subjects were told to respond first to the target word and then to the digit confirmed that this situation did not affect the results (see Appendix B). These stimuli sequences were displayed by the MEL program (Schneider, 1988). A training block of 24 items preceded each experimental task.…”
Section: Methodsmentioning
confidence: 99%
“…A control experiment, in which subjects were told to respond first to the target word and then to the digit confirmed that this situation did not affect the results (see Appendix B). These stimuli sequences were displayed by the MEL program (Schneider, 1988). A training block of 24 items preceded each experimental task.…”
Section: Methodsmentioning
confidence: 99%
“…The Lexical Salience Task (see below) was administered on a PC, programmed in MicroExperimental Laboratories (MEL, v. 2.01;Schneider, 1988), and run entirely within MS-DOS. A microphone, held in place by a gooseneck clamp and attached to the computer by a cable, measured vocal reading speed (ie onset of the vocal response).…”
Section: Apparatus and Materialsmentioning
confidence: 99%
“…Twenty-one participants from an introductory psychology course participated in the experiment for credit. Participants were tested on IBM-type personal computers, programmed with the MEL software (Schneider, 1988). Twenty-four problems (12 tree and 12 false) were constructed (see Appendix B): 8 problems with the addend 3, 8 with the addend 5, and 8 with the addend 7.…”
Section: Me~odmentioning
confidence: 99%
“…The data from the single no-transition participant were also preserved for separate analysis. All participants were tested on IBM-type personal computers, programmed with the Micro Experimental Language (MEL) software (Schneider, 1988).…”
Section: Me~odmentioning
confidence: 99%